Islamic Sukuk as a Tool for Development and Reconstruction in Libya (Journal of human and social sciences, 2023)
The search for financing sources for economic development and reconstruction in Libya is one of the main challenges facing post-2011 development plans, amid infrastructure damage, unstable public revenues, and the prioritization of salaries over development in the national budget. This study proposes Islamic sukuk as a tool for financing development and reconstruction in Libya, drawing on contemporary international experiences from Malaysia, Sudan, Saudi Arabia, and the UAE, using a comparative approach. The study presents a model of government participation sukuk called “Reconstruction Sukuk,” aimed at funding reconstruction and infrastructure projects, benefiting both economic development and sukuk holders. The study recommends establishing a legal framework for these sukuk, creating a supervisory authority to issue and monitor them, ensuring Sharia compliance, and raising public awareness about the importance of sukuk investment, free from usury concerns. Keywords: Islamic sukuk, economic development, reconstruction, Islamic finance, Libya.
Keywords: Islamic Sukuk; Islamic Financial Instruments; Infrastructure; Libyan Economy; Project Financing